Composite electrolyte taking ZIF-8 coated cellulose membrane as skeleton and preparation method thereof
By growing ZIF-8 material in situ on the cellulose membrane and casting the polymer electrolyte slurry on it, the shortcomings of the existing composite electrolyte in terms of ionic conductivity and mechanical properties are solved, and higher lithium ion transport capabilities and electrochemical properties are achieved.
Patent Information
- Application Number
- CN202411788563.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
The composite electrolytes of existing solid-state lithium metal batteries still cannot meet practical application requirements in terms of ionic conductivity and mechanical properties.
The ZIF-8 coated cellulose film was used as the skeleton of the composite electrolyte, and the ZIF-8 material was loaded onto the cellulose film by in-situ growth method, and the polymer electrolyte slurry was cast on the cellulose film by solution casting method.
It improves the transmission capacity of lithium ions, promotes ion conduction, enhances the mechanical properties and limit current density of composite electrolytes, and significantly improves the cycling stability of lithium symmetric batteries and the electrochemical performance of the whole battery.
Smart Images

Figure HDA0005174731100000011 
Figure HDA0005174731100000021 
Figure HDA0005174731100000031
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion battery electrolytes and relates to a composite electrolyte with a ZIF-8 coated cellulose film as a skeleton and a preparation method thereof. Background Art
[0002] In order to avoid the safety hazards of organic electrolytes such as flammable organic electrolytes in lithium-ion batteries using liquid electrolytes and to improve the energy density of batteries, solid-state lithium metal batteries have been developed. Solid electrolytes that match solid lithium metal are mainly divided into polymer electrolytes and inorganic electrolytes. Polymer electrolytes have the characteristics of good processability and flexibility, and can form a better contact interface with the electrode, but the room temperature ionic conductivity is low; inorganic solid electrolytes have a non-porous structure and high mechanical strength, which can prevent lithium dendrites from penetrating, and have ionic conductivity comparable to that of existing liquid electrolytes. However, the interface impedance between them and the electrodes is large, and there are also disadvantages such as high cost, difficulty in processing, high brittleness, and complex synthesis process. The composite polymer electrolyte formed by introducing inorganic fillers into polymer electrolytes provides a more reasonable solution. The ionic conductivity and lithium ion migration number of solid polymer electrolytes are improved to a certain extent after the addition of inorganic fillers. At the same time, the introduction of fillers also improves the mechanical properties and thermal stability of polymer electrolytes. However, the improved ionic conductivity and mechanical properties still cannot meet the practical application of solid lithium metal batteries, and need to be modified on this basis.
[0003] ZIF-8 is a new type of porous material composed of organic ligands and metal ions. It is widely used due to its unique properties, such as high specific surface area, open skeleton structure, high porosity and Lewis acid surface. Studies have shown that the large specific surface area and surface containing Lewis acid active sites of ZIF-8 are conducive to its adsorption of anions in lithium salts, providing channels for the transmission of lithium ions and promoting ion conduction. In addition, as an organic-inorganic hybrid material, the organic component can promote good compatibility between ZIF-8 materials and polymers, making them uniformly dispersed in the polymer matrix. Cellulose, as a biomass resource, has the advantages of being renewable, non-toxic and low-cost, and can effectively improve its mechanical properties and thermal stability without sacrificing ionic conductivity. ZIF-8 materials and cellulose are very conducive to the modification of composite electrolytes, providing new ideas for the development and application of new solid electrolytes. Summary of the invention
[0004] In order to solve the deficiencies of the above-mentioned prior art, the present invention provides a method for preparing a composite electrolyte with a ZIF-8 coated cellulose membrane as a skeleton, the purpose of which is to modify the composite electrolyte by ZIF-8 coated cellulose membrane, thereby improving the performance of the composite electrolyte.
[0005] To achieve the purpose, the present invention adopts the following technical solution:
[0006] The present invention first provides a method for preparing a composite electrolyte with a ZIF-8 coated cellulose membrane as a skeleton, comprising the following steps:
[0007] (1) dissolving zinc nitrate hexahydrate in methanol to obtain solution A; dissolving 2-methylimidazole in methanol to obtain solution B;
[0008] (2) After the cellulose membrane is soaked in solution A for 0.5 to 1 hour, solution B is added to solution A, the cellulose membrane is soaked for another 24 to 36 hours, then taken out, washed with ethanol, and dried to obtain a ZIF-8 coated cellulose membrane;
[0009] (3) dissolving a polymer precursor, a lithium salt, and a lithium lanthanum zirconium oxide filler in an organic solvent to obtain a polymer electrolyte raw material;
[0010] (4) After the ZIF-8 coated cellulose membrane obtained in step (2) is fully infiltrated in the polymer electrolyte raw material obtained in step (3), vacuum drying is performed to obtain a composite electrolyte with the ZIF-8 coated cellulose membrane as the skeleton.
[0011] Preferably, the concentration of zinc nitrate hexahydrate in the solution A in step (1) is 0.01-0.02 g / mL.
[0012] Preferably, the concentration of 2-methylimidazole in the solution B in step (1) is 0.03-0.04 g / mL.
[0013] Preferably, in step (2), solution A and solution B are mixed in a molar ratio of zinc nitrate hexahydrate to 2-methylimidazole of 1:8.
[0014] Preferably, the thickness of the cellulose separator in step (2) is 25 to 35 μm.
[0015] Preferably, in step (3), the ratio of the polymer precursor, lithium salt, lithium lanthanum zirconium oxide filler and organic solvent is 1 g: 0.4-0.5 g: 0.1-0.15 g: 10-12 mL.
[0016] Preferably, in step (3), the polymer precursor is one of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and polyethylene oxide (PEO), the lithium salt is one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium nitrate (LiNO3), lithium perchlorate (LiClO4) and lithium hexafluorophosphate (LiPF6), and the organic solvent is one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) and tetrahydrofuran.
[0017] The present invention also provides a lithium metal battery, which adopts the composite electrolyte with the ZIF-8 coated cellulose membrane as the skeleton.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0019] 1. The present invention uses ZIF-8 to coat the cellulose membrane to modify the composite electrolyte. ZIF-8 provides a channel for the transmission of lithium ions, promotes ion conduction, and increases the number of lithium ion migration. The cellulose membrane enhances the mechanical properties of the composite polymer electrolyte and increases the limiting current density. The cycle stability of the lithium symmetrical battery assembled with the modified composite electrolyte prepared by the present invention and the electrochemical performance (including cycle performance and rate performance) of the whole battery are significantly improved compared with the composite electrolyte not modified by coating the cellulose membrane with ZIF-8.
[0020] 2. The present invention uses an in-situ growth method to load the ZIF-8 material onto the cellulose membrane, and then casts the polymer electrolyte slurry on the cellulose membrane by a solution casting method. The method is simple, low-cost and has good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Figures a and b are SEM images of the original cellulose membrane and ZIF-8 coated cellulose membrane, respectively. Figure 1 Figures c and d are SEM images of the electrolytes prepared in Comparative Example 1 and Example 1, respectively.
[0022] Figure 2 Figure a and Figure b are the lithium ion migration number test diagrams of the electrolyte membranes prepared in Comparative Example 1 and Example 1, respectively.
[0023] Figure 3 This is a test diagram of the limiting current density of the electrolyte membrane prepared in Example 1 and Comparative Example 1.
[0024] Figure 4 This is a test chart of the lithium cycle stability of the electrolyte membrane prepared in Example 1 and Comparative Example 1.
[0025] Figure 5This is a test diagram of the charge and discharge cycle performance of the electrolyte membrane prepared in Example 1 and Comparative Example 1.
[0026] Figure 6 This is a rate performance test diagram of the electrolyte membrane prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0027] The present invention is described in detail below with reference to specific embodiments.
[0028] Example 1
[0029] In this example, a composite electrolyte with a ZIF-8 coated cellulose membrane as a skeleton was prepared according to the following steps:
[0030] (1) 0.5 g of zinc nitrate hexahydrate was dissolved in 30 mL of methanol to obtain solution A; 1.104 g of 2-methylimidazole was dissolved in 30 mL of methanol to obtain solution B.
[0031] (2) After soaking the cellulose membrane (thickness ~30 μm) in solution A at room temperature for 0.5 hours, solution B was added to solution A, and the cellulose membrane was soaked for another 24 hours before being taken out, washed with ethanol and dried to obtain a ZIF-8 coated cellulose membrane.
[0032] (3) Take 1 g of PVDF-HFP and dissolve it in 12 mL of NMP. Stir for 3 h, then add 0.4 g of LiTFSI and 0.1 g of LLZTO powder, and continue stirring for 4 h to obtain a polymer electrolyte raw material.
[0033] (4) The ZIF-8 coated cellulose membrane obtained in step (2) is fully soaked in the polymer electrolyte raw material obtained in step (3), dried under vacuum at 80° C. for 48 h, and cut into discs with a diameter of 16 mm to obtain a composite electrolyte with the ZIF-8 coated cellulose membrane as the skeleton.
[0034] Example 2
[0035] In this example, a composite electrolyte with a ZIF-8-coated cellulose membrane as a skeleton is prepared according to the method of Example 1, except that the N-methylpyrrolidone (NMP) in step (3) is replaced with an equal amount of N,N-dimethylformamide (DMF).
[0036] Example 3
[0037] In this example, a composite electrolyte with a ZIF-8-coated cellulose membrane as a skeleton is prepared according to the method of Example 1, except that the PVDF-HFP in step (3) is replaced with an equal amount of PEO.
[0038] Comparative Example 1
[0039] This comparative example prepared a composite electrolyte without ZIF-8 coated cellulose modification according to the following steps:
[0040] (1) Take 1 g of PVDF-HFP and dissolve it in 12 mL of NMP. Stir for 3 h, then add 0.4 g of LiTFSI and 0.1 g of LLZTO powder, and continue stirring for 4 h to obtain a polymer electrolyte raw material.
[0041] (2) The polymer electrolyte raw material was poured into a polytetrafluoroethylene mold, allowed to stand at room temperature for 1 hour, and then placed in a vacuum drying oven at 80° C. for 48 hours. The dried electrolyte membrane was demoulded and cut into discs with a diameter of 16 mm to obtain a composite polymer electrolyte membrane.
[0042] Figure 1 Figure a is the SEM image of the original cellulose membrane, and Figure b is the SEM image of the ZIF-8 coated cellulose membrane. It can be seen that ZIF-8 grows uniformly on the surface of the cellulose membrane through the in situ synthesis method. Figure 1 Figures c and d in the figure are SEM images of the electrolytes prepared in Comparative Example 1 and Example 1, respectively. It can be seen that the electrolyte prepared in Comparative Example 1 has a cellular crystal structure, while the electrolyte prepared in Example 1 is in an amorphous phase state with no obvious pores on the surface, indicating that the modified electrolyte membrane has a lower crystallinity and a smoother and denser surface. Lower crystallinity is conducive to promoting the transmission of lithium ions, while a smooth and dense surface is conducive to better contact between the electrolyte and the electrode interface, improving the ability to resist lithium dendrites, thereby improving the electrochemical performance of the electrolyte.
[0043] The lithium stability test of the electrolyte obtained in the embodiment was tested by assembling a Li||Li symmetrical battery. Specifically, the positive and negative electrodes both used lithium sheets as blocking electrodes, and were assembled into a CR2032 button battery in the order of negative electrode shell-lithium sheet-electrolyte-lithium sheet-steel sheet-spring-positive electrode shell. Test steps: first constant current charging for 30 minutes, then constant current discharge for 30 minutes, with a current density of 0.2 mA·cm -2 .
[0044] The charge-discharge cycle performance of the obtained electrolyte was tested by assembling a Li||LFP full battery, specifically: assembling a CR2032 button cell in the order of negative electrode shell-lithium sheet-electrolyte-lithium iron phosphate positive electrode-steel sheet-spring-positive electrode shell. Test process: cycle at 0.1C, voltage range 2.5-3.65V, cut-off current calculated as 0.05C.
[0045] Figure 2Figures a and b in the figure are the lithium ion migration test diagrams of the electrolyte membrane prepared in comparative example 1 and example 1, respectively. The it curve in the figure represents the DC polarization process of the electrolyte membrane, and the impedance curve is the fitting impedance spectrum curve before and after polarization of the electrolyte membrane. Figure 1 Calculate the lithium ion migration number t of the electrolyte membrane prepared in Example 1 Li+ is 0.49, while the lithium ion migration number t of the electrolyte membrane prepared in Comparative Example 1 is Li+ It is 0.20, which is much lower than that in Example 1. This is because the electrolyte in Example 1 uses ZIF-8 coated cellulose membrane as a skeleton, which promotes the transmission of lithium ions. A high lithium ion migration number is beneficial to reducing the influence of concentration polarization, ensuring the power output of the battery, and is beneficial to suppressing the concentration gradient, reducing voltage loss, and improving the rate performance of lithium ion batteries.
[0046] Figure 3 The limiting current density test diagram of the electrolyte membrane prepared in Example 1 and Comparative Example 1 is 0.750.2 mA·cm -2 and 1.350.2mA·cm -2 The presence of cellulose improves the mechanical properties of the electrolyte membrane and enhances its ability to resist lithium dendrite growth, thereby increasing its limiting current density.
[0047] Figure 4 and Figure 5 The lithium cycle stability test graph and the charge-discharge cycle performance test graph of the electrolyte membrane prepared in Example 1 and Comparative Example 1 are shown respectively. Figure 4 It can be seen that at 60°C and 0.20 mA cm -2 Under the test conditions, the composite electrolyte membrane with ZIF-8 coated cellulose membrane as the skeleton prepared in Example 1 can stably cycle for 800 cycles, showing good stability to lithium, while the composite electrolyte membrane prepared in Comparative Example 1 shows a larger polarization voltage during the cycle and is pierced by lithium dendrites after only 300 cycles, indicating that the modified electrolyte membrane has stronger resistance to lithium dendrites and stability to lithium. Figure 5 It can be seen that the composite electrolyte membrane with ZIF-8 coated cellulose membrane as the skeleton prepared in Example 1 has a maximum discharge capacity of 166.07 mA·h·g at 60°C and 0.1C. -1 After 100 cycles of charge and discharge, the discharge capacity is still 154.01 mA·h·g -1 The capacity retention rate is 92.7%, showing good cycle performance. The maximum discharge capacity of the composite electrolyte membrane prepared in Comparative Example 1 is 154.40 mA·h·g -1After 50 cycles, the discharge capacity dropped rapidly, and after 100 cycles, the capacity was only 94.21 mA·h·g -1 , the capacity retention rate is only 61.0%.
[0048] Figure 6 The figure is a rate performance test diagram of the electrolyte membrane prepared in Example 1 and Comparative Example 1. Figure 6 It can be seen that the composite electrolyte membrane with ZIF-8 coated cellulose membrane as the skeleton prepared in Example 1 has a discharge capacity much higher than that of the unmodified composite electrolyte membrane prepared in Comparative Example 1 at the rates of 0.1C, 0.2C, 0.5C, 1.0C and 2.0C, and when the charge and discharge rate returns to 0.1C, the discharge capacity remains unchanged, which is about 160 mA·h·g -1 The composite electrolyte membrane with ZIF-8 coated cellulose membrane as the skeleton showed better rate performance than the unmodified composite electrolyte membrane.
[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite electrolyte with a ZIF-8 coated cellulose membrane as a skeleton, characterized in that: The following steps are involved: (1) dissolving zinc nitrate hexahydrate in methanol to obtain solution A; dissolving 2-methylimidazole in methanol to obtain solution B; (2) After the cellulose membrane is soaked in solution A for 0.5 to 1 hour, solution B is added to solution A, the cellulose membrane is soaked for another 24 to 36 hours, then taken out, washed with ethanol, and dried to obtain a ZIF-8 coated cellulose membrane; (3) dissolving a polymer precursor, a lithium salt, and a lithium lanthanum zirconium oxide filler in an organic solvent to obtain a polymer electrolyte raw material; (4) After the ZIF-8 coated cellulose membrane obtained in step (2) is fully infiltrated in the polymer electrolyte raw material obtained in step (3), vacuum drying is performed to obtain a composite electrolyte with the ZIF-8 coated cellulose membrane as the skeleton.
2. The method for preparing a composite electrolyte with a ZIF-8 coated cellulose membrane as a skeleton according to claim 1, characterized in that: The concentration of zinc nitrate hexahydrate in the solution A in step (1) is 0.01-0.02 g / mL.
3. The method for preparing a composite electrolyte with a ZIF-8 coated cellulose membrane as a skeleton according to claim 1, characterized in that: The concentration of 2-methylimidazole in the solution B in step (1) is 0.03-0.04 g / mL.
4. The method for preparing a composite electrolyte with a ZIF-8 coated cellulose membrane as a skeleton according to claim 1, characterized in that: In step (2), solution A and solution B are mixed in a molar ratio of zinc nitrate hexahydrate to 2-methylimidazole of 1:
8.
5. The method for preparing a composite electrolyte with a ZIF-8 coated cellulose membrane as a skeleton according to claim 1, characterized in that: The thickness of the cellulose membrane in step (2) is 25 to 35 μm.
6. The method for preparing a composite electrolyte with a ZIF-8 coated cellulose membrane as a skeleton according to claim 1, characterized in that: In step (3), the ratio of the polymer precursor, lithium salt, lithium lanthanum zirconium oxide filler and organic solvent is 1g: 0.4-0.5g: 0.1-0.15g: 10-12mL.
7. The method for preparing a composite electrolyte with a ZIF-8 coated cellulose membrane as a skeleton according to claim 1, characterized in that: In step (3), the polymer precursor is one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene and polyethylene oxide, the lithium salt is one of bis(trifluoromethanesulfonyl)imide lithium, bis(fluorosulfonyl)imide lithium salt, lithium nitrate, lithium perchlorate and lithium hexafluorophosphate, and the organic solvent is one of N-methylpyrrolidone, N,N-dimethylformamide and tetrahydrofuran.
8. A composite electrolyte having a ZIF-8 coated cellulose membrane as a skeleton, obtained by the preparation method according to any one of claims 1 to 7.
9. A lithium metal battery, characterized in that: The composite electrolyte with the ZIF-8 coated cellulose membrane as the skeleton as described in claim 8 is used.
Citation Information
Patent Citations
Solid-state electrolyte composite membrane, preparation method and application thereof
CN111370753A
Cellulose-based composite film and preparation method thereof
CN116487822A
MOF (Metal Organic Framework) modified bacterial cellulose composite membrane as well as preparation and application thereof
CN118630424A
Solid electrolyte based on dual-functional MOF three-dimensional nanofiber material and preparation method and application thereof
CN119009102A